Work-life balance among the employees: a case study of Indian automobile industry - Ravichandran, Saranya (2024)
In the world of work, the importance of work-life balance in the workplace has gained substantial recognition, driven by policymakers' increasing awareness of the challenges faced by workers in reconciling their personal and professional responsibilities. This awareness was ignited by the transition from the traditional "male breadwinner model" to the "dual earner model," where all adults are expected to engage in paid work. While this shift reduced women's financial dependency on men, it introduced new challenges, leading to a "double shift" for many women—juggling paid employment with unpaid household duties (International Labour Organization, 2022). Working hours vary considerably across countries and industries, with European nations typically favouring shorter workweeks, such as Sweden's recent experimentation with 6-hour workdays, while Asian and American countries tend to have longer hours. Australia and New Zealand, among others, prioritize work-life balance, resulting in shorter workweeks, and New Zealand has even piloted a four-day workweek to enhance well-being and job satisfaction for employees (Nicola-mills, 2018). This research paper focuses on work-life balance within the demanding Indian automobile industry, recognizing its significant impact on employee well-being and overall organizational performance. The study employs primary and secondary data collection methods, including structured questionnaires, to gather insights from a diverse range of employees. It conducts a comprehensive review of existing literature, industry reports, and statistical data to gain a thorough understanding of the subject. The findings shed light on how employees in this industry manage the delicate balance between work and personal life, examining factors such as workload, job flexibility, organizational culture, and support systems. Additionally, the study explores the effects of work-life balance on employee well-being, job satisfaction, productivity, and its influence on financial metrics like Return on Investment (ROI) and Return on Expectation (ROE). An evaluation of current work-life balance practices identifies areas for improvement, while considering the influence of social and cultural factors in the Indian context. The results of this research provide significant new perspectives on how employees in the Indian automobile industry experience work-life balance. The results of the study have implications for work-life balance management on both a theoretical and practical level. It is suggested that organizations in the automotive industry improve their work-life balance practices to foster a healthier workplace and increase productivity and employee well-being. This research paper aims to support a more balanced and long-term work culture within the sector and lay a foundation for future research. The information from this study can help managers, policy makers, and human-resources professionals develop strategies and policies to give employees in the Indian automobile industry a supportive and fulfilling workplace.